Efficacy of pre-insemination treatment with GnRH for improving conception rate in repeat breeder cows - SHELAR, R R; DEOPURKAR, V L; BAKSHI, S A; GULAWANE, S U (The Indian Journal of Animal Reproduction, 2023)
An attempt was made to asses pre-insemination use of Gonadotropin Releasing Hormone (GnRH) in 20noninfectious repeat breeding Gir Cows and its crossbreds (G x HF, G x J ). Buserline 10 ug was injectedintramuscularly just before insemination in treatment group of animals. Conception rate in the treatment groupwas 20% higher than the control. GnRH had no influence on subsequent serum progesterone level on 14th and. 22nd day post-insemination. The properties of estrual mucus discharge (pH, Spinnbarlceit test and in-vitro spermpenetration test) differed significantly between fertile and nonfertile estrus.
Keywords: Repeat breeding; GnRH; cows; conception